Management of irregular sharp molars in a buffalo – A case report - Ramesh, P.; Kumar, P. Ravi; Raghunath, M.; Sagar, P. Vidya (Buffalo Bulletin, 2016)
A four year old Graded Murrah Buffalo was presented with a history of bilateral distension of cheeks, persistent salivation and occasional quidding since one year. Physical examination revealed asymmetrical hard bulge of the both cheeks which was pitting on pressure. Upon oral examination noticed abnormal accumulation of feed material on either side of the cheeks, ulcerative lesions in oral mucosa and irregular sharp molars. The impacted material from both the sides of buccal cavity was removed and irrigated with potassium permanganate solution. The irregular sharp edges of the teeth were rasped by tooth rasp manually to level the teeth, resulting in complete recovery.